SUSTAINABILITY VALUE CHAIN IN BIOECONOMICS - N. Penev; Y. Andreev (Trakia Journal of Sciences)
The concept of bioeconomics covers all sectors of the economy, including agriculture, which supplies renewable resources: plants, animals, microorganisms and their processed products. The goal is a transition to an economy that is independent of fossil fuels and non-renewable resources. Agriculture and forestry, fisheries and aquaculture, as well as the conversion of biotechnological biomass and biological waste, are central to the multilateral new value chain. The processing industry uses renewable resources in various products, in particular, due to the industrial application of biotechnological and microbiological processes, especially in the chemical industry. This also applies to the food, woodworking, paper, construction, leather, and textile industries, as well as parts of the pharmaceutical and energy industries. Thus, the cyclic system and the storage of reusable waste are also included in the bioeconomic system. The aim of our study is to study the degree of development of sustainable value chains in bioeconomics.